A Novel Electrophototrophic Bacterium Rhodopseudomonas palustris Strain RP2, Exhibits Hydrocarbonoclastic Potential in Anaerobic Environments - Venkidusamy, Krishnaveni; Megharaj, Mallavarapu (Frontiers in Microbiology, 2016)
An electrophototrophic, hydrocarbonoclastic bacterium Rhodopseudomonas palustris stain RP2 was isolated from the anodic biofilms of hydrocarbon fed microbial electrochemical remediation systems (MERS). Salient properties of the strain RP2 were direct electrode respiration, dissimilatory metal oxide reduction, spore formation, anaerobic nitrate reduction, free living diazotrophy and the ability to degrade n-alkane components of petroleum hydrocarbons in anoxic, photic environments. In acetate fed microbial electrochemical cells, a maximum current density of 305±10 mA/m2 (1000Ω) was generated (power density 131.65±10 mW/m2) by strain RP2 with a coulombic efficiency of 46.7 ± 1.3%. Cyclic voltammetry studies showed that anaerobically grown cells of strain RP2 is electrochemically active and likely to transfer electrons extracellularly to solid electron acceptors through membrane bound compounds, however, aerobically grown cells lacked the electrochemical activity. The ability of strain RP2 to produce current (maximum current density 21±3 mA/m2; power density 720±7 µW/m2, 1000Ω) using petroleum hydrocarbon (PH) as a sole energy source was also examined using an initial concentration of 800 mg l-1 of diesel range hydrocarbons (C9- C36) with a concomitant removal of 47.4 ± 2.7% hydrocarbons in MERS. Here, we also report the first study that shows an initial evidence for the existence of a hydrocarbonoclastic behavior in the strain RP2 when grown in different electron accepting and illuminated conditions (anaerobic and MERS degradation). Such observations reveal the importance of photoorganotrophic growth in the utilization of hydrocarbons from contaminated environments. Identification of such novel petrochemical hydrocarbon degrading electricigens, not only expands the knowledge on the range of bacteria known for the hydrocarbon bioremediation but also shows a biotechnological potential that goes well beyond its applications to MERS.